An affine macro-finance term structure model for the euro area - Wolfgang Lemke (Deutsche Bundesbank, 2007)
A joint model of macroeconomic and term structure dynamics is specified and estimated for the euro area. The model comprises a backward-looking Phillips curve, a dynamic IS equation, a monetary policy rule as well as a specification of the dynamics of trend growth and the natural real interest rate. Under the condition of no arbitrage, yields of all maturities are affine functions of the macroeconomic driving forces. With the exception of a shock to potential output growth, the response of short-term yields to macroeconomic shocks is generally stronger than that of long-term yields. Impulse responses of all bond yields are fairly persistent, which reflects the persistence of their macroeconomic driving forces. Across the whole maturity spectrum, about ninety percent of the variation in yields is explained jointly by monetary policy shocks and shocks to the natural real rate of interest; the relative contribution of the latter shock increases with time to maturity. Cost-push shocks explain at most eight percent, while shocks to the output gap play an even less important role.
Keywords: E32; G12; E43; 330; affine term structure models; monetary policy; euro area; Zinsstrukturtheorie; Ökonometrisches Makromodell; Geldpolitik; Reaktionsfunktion; Schätzung; EU-Staaten